Development of a Family-Based Early Intervention Program to Develop Sign Language Skills in Deaf Children - Rajani, Rini (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Family-based early intervention needs to be provided for children who experience obstacles, this aims to ensure that the obstacles experienced by children can be overcome from an early age. The obstacles that are overcome from now on will have a positive impact in the future development. This research aims to develop a family-based intervention program to develop sign language skills for deaf children. The research method used in this research is the descriptive qualitative method. The subject in this study was a 5-yearold deaf child and the child's parents. The results of this research are an intervention program based on family resources to develop deaf children's sign language skills as a modality for children to communicate with the community and a modality in educational settings in elementary schools. It is hoped that this research can help deaf children, parents, and teachers to develop sign language skills in deaf children.